Adventures of A Photographer from Madeira in the Imperial Court of Brazil (International Journal on Stereo & Immersive Media, 2020)
Based on the discovery of four portraits in the collection of the Brazilian National Archives, we researched the trajectory of DiogoLuis Cipriano (1820-1870), born on Madeira Island, one of the first daguerreotypists to settle in Rio de Janeiro. We try to describethe tensions and conflicts between painters, miniaturists and photographers in search for their prestige and commercial successin the capital of the Empire of Brazil, between 1850 and 1870. On the other hand, we analyze how in the public arena of thenewspaper pages and the busy corners of the Court, techniques are confronted, talents are measured and, mainly, the signs ofmodernity and the monopoly of saudade (nostalgia) are disputed. Resumo:A partir da descoberta de quatro retratos na coleção do Arquivo Nacional brasileiro, investigamos a trajetória de Diogo LuisCipriano (1820-1870), nascido na Ilha da Madeira, um dos primeiros daguerreotipistas a se estabelecer no Rio de Janeiro.Procuramos descrever as tensões e os conflitos entre pintores, miniaturistas e fotógrafos por prestígio e sucesso comercial nacapital do Império do Brasil, entre 1850 e 1870. Por outro lado, observamos como na arena pública das páginas dos jornais edas movimentadas esquinas da Corte confrontam-se técnicas, medem-se talentos e, principalmente, disputam-se os signos demodernidade e o monopólio da saudade.